Issues on loop prevention in MPLS networks. - Ohba, Y. (IEEE Communications magazine)
In multiprotocol label switching (MPLS) networks, data packets are forwarded through label-switched paths (LSPs) which are set up using a label distribution protocol. Since any label distribution protocol makes use of information obtained from the layer 3 routing protocol, and the routing protocol may not be loop-free, there is a possibility of an LSP forming a loop. This article focuses on MPLS loop prevention by which LSPs are prevented from forming loops. Especially, two loop prevention algorithms that have been proposed to the IETF are simulated to investigate the number of control messages required for setting up or reconfiguring LSPs over an actual routing protocol